PENGARUH IKLIM ORGANISASI TERHADAP LOYALITAS KARYAWAN DI HOTEL KERATON RESORT DAN SPA BADUNG - Andreas RatoKawaleka (STIE BIITM, 2019)
Organizational climate is a condition that exists within the organization or company. Organizational climate can be measured in the work environment both directly and indirectly affect employees and their work, in other words, the organizational climate will affect the motivation and behavior of employees who will create loyalty to these employees. This research aimed to analyze the influence of Organizational Climate On Employee Loyalty at Hotel Keraton Resort and Spa Badung. The sample of this research is 60 employee who worked more than 10 years at Hotel Keraton Resort and Spa Badung. The Data sources used in this research are primary and secondary data. Data is analyzed using path analysis that is assisted with SPSS for Windows version 22. Data collection method in this research using interview method, by means of questionnaires with likert scale. The analytical technique used is simple linier regression analysis. Results of statistical analysis known that the organizational climate influenced on employee loyalty is 20,8%, based on hypothesis testing with t-test results, it can be concluded that the organizational climate variable (X) partially and significantly positive influenced on employee loyalty variable (Y) with value of t-test is 3,898 and sig. 0,000 at Hotel Keraton Resort and Spa Badung